A religião como alienação e ideologia no jovem Marx: um estudo sobre os Manuscritos Econômico-filosóficos de 1844 e A Ideologia Alemã de 1846 - Nunes Júnior, Carlos Alberto (2021)
The theme around which this research is focused is the investigation of the criticism of religion that Karl Marx writes in his books Economic and Philosophic Manuscripts of 1844 and The German Ideology (1845-1846), the latter in partnership with Friedrich Engels. We understand here that there is no systematization of his criticism, but that did not preclude a deliberate examination of what religion is and what its role in society is. To achieve the objective, it is necessary, first, to analyze the criticism of religion developed by Ludwig Feuerbach in The Essence of Christianity (1841). Feuerbach's analysis of religion exposes the religious alienation of the human who cannot identify with his own essence and projects it into an illusion that will be called God, so that it would be necessary to overcome religion, through atheism, to end alienation, since the human would return to meet its generic essence without resorting to a fictitious intermediary. The Feuerbachian examination has a strong impact on Marx and Engels and there is no way to understand their assessment of religion without ever addressing Feuerbach, including the confession by Engels who years later declares that both he and Marx, they were momentarily Feuerbachian. In a second step, it is necessary to understand the concept of alienation in Marx, identifying what would be the approximations and distances between the Marxian and Feuerbachian usage for the concept of alienation, because in Marx religious alienation is a symptom of the alienation of work. Thus, there would be no way to overcome the strangeness caused by religion without overcoming the previous form of alienation, that is, in Marx, religious alienation could not be overcome through an individual change of conduct. At the same time that Marx is influenced by Feuerbachian humanism, the idea that the human has lost himself and needs to rediscover his essence. Finally, to understand how Marx and Engels analyze the concept of ideology and its respective relationship with religion, since ideology would be an ideal representation of material explorations, a way for the ruling class to perpetuate its domination. Thus, it is necessary to understand the origin of the ideology and its impact on consciousness. After these three moments, we will have finished tracking and analyzing criticism of religion in young Marx.